Validação do diagnóstico de enfermagem: eliminação urinária prejudicada com foco em lactentes - Miranda, Francine Ramos de (Universidade Federal de São Carlos, 2013)
It is known that the observation of the urinary elimination of child in routine pediatric clinic helps identify human responses and thereby prevent complications present and future. It can be inferred that the analysis of the nurse on the urinary elimination of child and accuracy in the preparation of nursing diagnoses (ND) is of fundamental importance. With respect to Impaired Urinary Elimination (IUE) NANDA- I, Inc, it may be identified the possibility of gaps, especially for infants with disorders urinary elimination, insofar as this population has particulars on how exhibit this problem. Thus, this study was aimed at making the concept analysis, validation by experts and observation of the proposed Impaired Urinary Elimination DE by NANDA- I, Inc. This is a descriptive study of validation of nursing diagnoses, based on the model proposed by Hoskins, but with adaptations. For the development of the concept analysis was performed a literature review in the databases LILACS, PubMed, CINAHL, and Cochrane Library, trying to select studies that founding the concept analysis based on the model of Walker and Avant, which proposes an investigation of the basic elements of an concept developed in eight steps. It were eligible 25 studies to conduct the concept analysis . To perform the analysis of all elements of diagnosis, it were also consulted 2 books of Pediatric Urology, 2 books on human physiology and 2 dictionaries of medical terms. The validation was performed by experts based on validation by consensus, which is a process whereby it is obtained the opinion or agreement between the author and a group of at least three experts. Interview was also conducted with 10 accounted for infants with urinary changes regarding the presence of the defining characteristics identified in concept analysis. As a result of CA it was identified that the concept was used IUE more frequently by medicine and its specialties and in a quantity less expressive by nursing. The defining attributes identified were: fever, urinary retention, weak urinary stream, inconsolable crying, crying during urination, irritability, hematuria, fetid urine, dysuria perception by parents and urination drip, among others. Among the antecedents identified are: urinary tract dilatation, hydronephrosis, genitourinary malformations, pyelonephritis, obstructive uropathy, urinary tract infection, vesicoureteral reflux, among others. The main effects were: weight loss, renal failure, acute renal parenchyma, growth deficiency and decreased renal function. From the data of CA it were suggested changes in wording of dysuria and DC including new DC. The proposed amendments after AC were analyzed by 10 experts. For selection and scoring of the experts it was used the scale proposed by Fehring in which the experts must reach at least 5 points. Of the 10 selected expert, 60% achieved a score of 5 to 7 points and 40% reached a score of 10 to 14 points. As a result of this step, among the DC proposed by NANDA I, Inc, it were validated urinary retention and dysuria . It was proposed a new wording for dysuria defining characteristic, namely, dysuria (in infants, crying when urinating or reporting parental perception of dysuria in infants). From the new proposed DC it were validated hematuria, fetid urine, anuria, oliguria, irritability and fever. It have also been suggested new DC by the experts. Regarding Factors Related (FR), from those proposed by NANDA-I, Inc just FR multiple causes has not been validated. The clinical stage was composed of a sample of 10 infants, 5 boys and 5 girls, 40% aged 1-3 months, 20% at age 5-7 months and 40% at age 8 to 12 months. The most part of medical diagnoses found was that of Urinary Tract Infection (UTI). The DC found most frequently were: fever (80%), crying during urination (60%), strain during urination (60%) and oliguria (50%). The results can contribute to improving the care of infants presenting dysfunction in the elimination of urine, leading to appropriate interventions in this population and promoting a safe care by seeking satisfactory results.
Validation of the nursing diagnosis impaired urinary elimination with a focus on infants
Keywords: Diagnóstico de enfermagem; Estudos de validação; Excreção urinária; Lactentes; Enfermagem pediátrica; Nursing diagnosis; Validation studies; Urinary elimination; Infant; Pediatric Nursing; CIENCIAS DA SAUDE::ENFERMAGEM